Karakteristik Pasien Nodul Tiroid di RS Ngoerah Denpasar - Juvita Novia; Wira Gotera; Ida Bagus Aditya Nugraha (STIKES Syedza Saintika Padang, 2025)
Thyroid nodules are the most common endocrine neoplasia seen in the clinic. The prevalence of thyroid nodules increases with age, sex, history of radiation exposure, family history, and other factors. The purpose of this study was to determine the prevalence and characteristics of patient with thyroid nodule at Ngoerah Hospital based on laboratory, ultrasonography and histopathology. This descriptive observational study involved 40 subjects. Data were obtained from the medical records of outpatient thyroid nodules who visited the Diabetes Polyclinic and inpatients at Ngoerah Hospital. The data collection was carried out within 3 months, from 1 December 2022 until 28 February 2023. The subjects consisted of 6 males (15%) and 34 females (85%), average age was 48 years and average nodule size was 3.9 cm. Thyroid hormone function was found most in 30 subjects (75%) euthyroid. Ultrasound using Ti-RADS score classification, 14 subjects were moderately suspicious (35%) and the same percentage for not suspicious group. FNAB using Bethesda classification, majority 23 subjects (57.5%) were benign. Histopathological showed 21 subjects (52.5%) were adenomatous struma. The highest proportion according to hormone function was euthyroid, moderately suspicious and not suspicious based on ultrasonography, nodule was benign based on FNAB, and adenomatous struma based on histopathology.